Quantitative easing, negative interest rates and money creation. What central banks can and cannot do? - Mariusz Kapuscinski; Dorota Scibisz (Institute of Economic Research (IER), 2016)
Since the Great Recession some central banks have introduced measures such as quantitative easing (QE) and negative interest rates which seem unconventional in terms of the pre-crisis monetary policy consensus. Some economists and policymakers expect these actions to affect the money supply, both directly and indirectly. The paper confronts these statements with some institutional constraints on money creation to examine whether the claimed influence on money supply is possible. Some types of QE could affect the money supply, however it should not be perceived as an incentive for commercial banks to increase lending. When it comes to the negative policy rates, the effect on banks' lending might actually be quite the opposite to the expected growth. These discrepancies result from certain inaccurate beliefs about money creation. Some adjustments provide a more realistic view of possible consequences of unconventional monetary policies and may contribute to the better implementation of monetary policy at the zero-lower bound.
Keywords: E51; E52; E58; 330; quantitative easing; negative interest rates; money creation; monetary transmission